Age differences in effects of family structure and quality on attachment to romantic partners and attitudes towards marriage and divorce - Kamenov, Željka; Jelić, Margareta (2010)
The aim of this research was to examine the differences in attachment to romantic partners and attitudes towards marriage and divorce among individuals whose parents had divorced as opposed to those whose parents had high quality marriages and those whose parents had low quality marriages, as well as to find out whether these effects of family structure and the quality of relationship between parents vary with age. A total of 1385 participants (432 high-school students, 529 undergraduate students from various faculties of the University of Zagreb, and 424 adults) were included in the research. Data about family structure and the quality of parental relationship were obtained. The modification of the Experiences in Close Relationship Inventory and Attitudes toward marriage and divorce scales were applied. Significant differences were found on Anxiety in attachment to romantic partners due to low quality of relationship between parents. Specifically, individuals whose parents had low marital quality while they were teenagers appear to be more anxious in their romantic relationships in comparison with individuals from two other types of families. There were also significant differences in attitudes towards marriage and divorce in regard to family type, but these effects were stronger in younger age groups. Overall, the quality of relationship between parents proved to be more important factor for future romantic relationships than family structure, with more immediate effects on attitudes toward marriage and divorce, and long term effects on romantic attachment.
Projekt MZOS
ENG